(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This article discusses the historical usages of “civilization” and “culture” and various definitions advanced by thinkers such as Oswald Spengler, FernandBraudel, and Philip Bagby, while alsosuggesting a new way of dealing with these two terms. The argument is that “civilization” is the key term todenote groups and peoples who share alarge and common geographic locus, values and social institutions, and that“culture” refers to a particular set of values or beliefs within the larger historico-cultural entity that is a civilization. If we treat “civilization” as the largest and highest socio -historical unit and “culture” as something smaller, lower, and subsumed under “civilization,” wewill better understand the ubiquitousphenomenon of cultural appropriation and civilizational hybridization. To further elucidate how these two terms should be understood and to disentangle themfrom each other, the essay provides an historical account of the context inwhich each term arose.